Pharmacokinetics and pharmacodynamics of antimalarial drugs in pregnant women - Kloprogge, F (2013)
Malaria is the most important parasitic disease in man and it kills approximately 2,000 people each day. Pregnant women are especially vulnerable to malaria with increased incidence and mortality rates. There are indications that pregnancy alters the pharmacokinetic properties of many antimalarial drugs. This is worrisome as lower drug exposures might result in lowered efficacy and lower drug exposures can also accelerate the development and spread of resistant parasites. The aim of this research was to study the pharmacokinetics and pharmacodynamics of the most commonly used drugs for the treatment of uncomplicated Plasmodium falciparum malaria during the second and third trimester of pregnancy using a pharmacometric approach. This thesis presents a number of important findings that increase the current knowledge of antimalarial drug pharmacology and that may have an impact in terms of drug efficacy and resistance. (1) Lower lumefantrine plasma concentrations at day 7 were evident in pregnant women compared to that in non-pregnant patients. Subsequent in-silico simulations with the final pharmacokinetic-pharmacodynamic lumefantrine/desbutyl-lumefantrine model showed a decreased treatment failure rate after a proposed extended artemether-lumefantrine treatment. (2) Dihydroartemisinin exposure (after intravenous and oral administration of artesunate) was lower during pregnancy compared to that in women 3 months post-partum (same women without malaria). Consecutive in-silico simulations with the final model showed that the underexposure of dihydroartemisinin during pregnancy could be compensated by a 25% dose increase. (3) Artemether/dihydroartemisinin exposure in pregnant women was also lower compared to literature values in non-pregnant patients. This further supports the urgent need for a study in pregnant women with a non-pregnant control group. (4) Quinine pharmacokinetics was not affected by pregnancy trimester within the study population and a study with a non-pregnant control group is needed to evaluate the absolute effects of pregnancy. (5) Finally, a data-dependent power calculation methodology using the log likelihood ratio test was successfully used for sample size calculations of mixed pharmacokinetic study designs (i.e. sparsely and densely sampled patients). Such sample size calculations can contribute to a better design of future pharmacokinetic studies. In conclusion, this thesis showed lower exposures for drugs used to treat uncomplicated Plasmodium falciparum malaria during the second and third trimester of pregnancy. More pharmacokinetic studies in pregnant women with a non-pregnant control group are urgently needed to confirm the current findings and to enable an evidence-based dose optimisation. The data-dependent power calculation methodology using the log likelihood ratio test can contribute to an effective design of these future pharmacokinetic studies.